THE RECEPTION OF MIGUEL DE CERVANTES’ LITERARY OUTPUT IN MACEDONIAN (Journal of Contemporary Philology, 2020)
This paper examines the translations of some of Miguel de Cervantes’ literary output in Macedonian. I trace the first abridged editions of Don Quijote from the 1950s and critically examine and assess the first and only unabridged edition of 1985 by Ilija Korubin and Aleksandar Mitevski. I also review the 2012 unabridged edition of his Novelas ejemplares, translated by Violeta Jagev, and finally, analyze verses from his plays and prose included in Deset veka na španskata poezija, an anthology of Spanish poetry translated by Mateja Matevski. The analysis shows that Cervantes’ literary output is underrepresented in the Macedonian culture, in comparison with other great names of world literature. Considering that the words ‘donkihotski’ and ‘donkihotstvo’ form part of the Macedonian language and are used in many contexts, a closer look is taken at the unabridged edition of Don Quijote in Macedonian.
Keywords: Miguel de Cervantes; Don Quijote; Novelas ejemplares; translation; reception